The Role of Alliances in the American – Chinese competition in southeast Asia between 1950 and 1954 (Damascus University Journal of Historical Studies, 2023)
Competition is a situation where two or more international parties decide to achieve benefits and interests according to rational calculations without resorting to the use of military force. The competition aims to achieve a high degree of efficiency at the lowest costs, thus pushing the competing forces to develop and improve their performance by focusing on technological innovations and innovations.The US-Chinese relations represent a clear example of international competition during the Cold War (1945-1991), as the United States of America considered China its first competitor in the Southeast Asia region, while Beijing viewed the United States of America as a hegemonic superpower seeking to contain and limit the Asian powers, particularly China.The American and Chinese sides sought to limit the power and influence of the other party by using many diplomacy, including the diplomacy of alliances, as Washington and Beijing found alliances a successful way to achieve their goals and interests in the region.While China tended to ally with the Soviet Union, and the two parties signed the Treaty of Alliance and Friendship in 1950, the United States of America tended to ally with Japan, Australia, New Zealand, Taiwan, Indonesia and a number of East Asian countries.It is worth noting that China’s need for military and economic assistance and its Marxist Leninist doctrine prompted it to ally with the Soviet Union, and therefore Beijing abandoned this alliance when it got what it wanted, while the United States of America took advantage of the East Asian countries’ need for military and economic assistance to impose the alliance on them, with the aim of sharing The US administration has the burden of defending its interests in the region.
Keywords: competition; alliances; the United States of America; China